C - ORGANIC DISTRIBUTION AS A SOURCE OF METHANE EMISSIONS IN WONOGIRI RESERVOIR - Wawan Herawan; Heni Rengganis (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
Sources of methane emissions from reservoirs are still not widely known in Indonesia. The Research regarding the methane emission source in undated reservoirs is very important to be done to gain data and information, therefore the global warming issues that associated with the methane emission can be solved. This paper discussing about the methane gas emissions that is influenced by the spread of C-organic at the Wonogiri reservoir. Identification of the availability of C-organic, water and sludge sampling was taken at some locations supposed to represent similar conditions. Results of labolatory analysis indicated that the magnitude of the methane production is highly dependent on the C-organic inputs from the water inflow of river catchment or activities involving organic material in the reservoir. Highest potential of methane production was encountered at the river mouth of Kali Kedawung and near the floating fish cultivation. Total potential of methane production of water in the Wonogiri reservoir is at an elevation of 134.7 m with 321.75 million m3 of water volume and 50 km2 of surface water area, stored a methane production of approximately 437.6 tonnes. Mitigation of methane emissions is to be done by reducing C-organic inputs to the reservoir by controlling the land-use in the catchment and reduce floating fish cultivation in the reservoir.